Stabilization of a mixed iron vanadium based hexagonal tungsten bronze hydroxyfluoride HTB–(Fe0.55V0.45)F2.67(OH)0.33 as a positive electrode for lithium-ion batteries. Issue 24 (9th June 2020) - Lemoine, Kévin; Moury, Romain; Lhoste, Jérôme; Hémon-Ribaud, Annie; Leblanc, Marc; Grenèche, Jean-Marc; Tarascon, Jean-Marie; Maisonneuve, Vincent
Abstract : The first mixed iron vanadium hydroxyfluoride with a Hexagonal Tungsten Bronze (HTB) structure as positive electrode reveals a capacity of 181 mA h g −1 . Unlike pure iron hydroxyfluoride the HTB network is partially maintained upon cycling. Abstract : In our search for novel insertion compounds for Li-based batteries, we have identified a new mixed iron vanadium based Hexagonal Tungsten Bronze (HTB) type phase. Its synthesis involves two steps which consist first of preparing mixed metal hydrated fluoride Fe1.64 V1.36 F8 (H2 O)2 by a microwave assisted thermal process, followed by thermal treatment under air to obtain metastable HTB–(Fe0.55 V0.45 )F2.67 (OH)0.33 hydroxyfluoride. 57 Fe Mössbauer spectrometry demonstrates the presence of oxidation states Fe 2+ and Fe 3+ in Fe1.64 V1.36 F8 (H2 O)2 as opposed to only Fe 3+ in HTB–(Fe0.55 V0.47 )F2.67 (OH)0.33 . Moreover, the Mössbauer spectra recorded at 77 K reveal that none of the compounds shows magnetic ordering owing to the presence of V 3+ distributed over the crystallographic sites of Fe 3+ . Complementary X-ray spectroscopy and Rietveld refinement further confirm the successful synthesis of HTB–(Fe0.55 V0.45 )F2.67 (OH)0.33 . Electrochemically, the new HTB–(Fe0.55 V0.45 )F2.67 (OH)0.33 shows a first discharge capacity of 181 mA h g −1 with 67% of this capacity remaining upon cycling. Unlike HTB–FeF2.66 (OH)0.34, the structure remains stable after the first discharge confirming the positive effect of vanadium in the HTB network.